Bayesian Probabilistic Projection of International Migration. - Azose, Jonathan; Raftery, Adrian; Azose, Jonathan J; Raftery, Adrian E (Demography (Springer Nature), 2015)
We propose a method for obtaining joint probabilistic projections of migration for all countries, broken down by age and sex. Joint trajectories for all countries are constrained to satisfy the requirement of zero global net migration. We evaluate our model using out-of-sample validation and compare point projections to the projected migration rates from a persistence model similar to the method used in the United Nations' World Population Prospects, and also to a state-of-the-art gravity model.